Pemahaman Hadis tentang Larangan Menggunakan Parfum bagi Perempuan Dengan Pendekatan Sosio Historis - Amliyah Widya Mahanani,; Muhid,; Andris Nurita, (Tahdis: Jurnal Kajian Ilmu Al-Hadis, 2023)
This article discusses the understanding of the hadith prohibition of using perfume for women which is often understood textually as the hadith editors read. The research method used in this article is by using qualitative methods with library research through content analysis from a socio-historical approach. Regarding the hadith about the prohibition of using perfume for women if interpreted textually becomes irrelevant today because perfume is part of body hygiene even though in its use it is forbidden to overdo it. So to interpret the hadith is to retrace the socio-historical aspect of the emergence of hadith texts prohibiting women from using perfume.